2018
DOI: 10.3390/s18010203
|View full text |Cite
|
Sign up to set email alerts
|

An Over 90 dB Intra-Scene Single-Exposure Dynamic Range CMOS Image Sensor Using a 3.0 μm Triple-Gain Pixel Fabricated in a Standard BSI Process

Abstract: To respond to the high demand for high dynamic range imaging suitable for moving objects with few artifacts, we have developed a single-exposure dynamic range image sensor by introducing a triple-gain pixel and a low noise dual-gain readout circuit. The developed 3 μm pixel is capable of having three conversion gains. Introducing a new split-pinned photodiode structure, linear full well reaches 40 ke−. Readout noise under the highest pixel gain condition is 1 e− with a low noise readout circuit. Merging two si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
(10 reference statements)
0
12
0
Order By: Relevance
“…Notably, the high EQE covering the near-infrared region is better than most commercial silicon-based imaging sensors, which are potential applications in mobile-phone-based facial recognition and surveillance cameras . Regarding dynamic range behavior, Sn-rich binary PVSK–PDs achieve an dynamic range of 100 dB (see Figure S11), which is better than that of commercial imaging sensors (∼60 dB) and is comparable to state-of-the-art wide-dynamic-range imaging sensors (∼100 dB). …”
Section: Resultsmentioning
confidence: 95%
“…Notably, the high EQE covering the near-infrared region is better than most commercial silicon-based imaging sensors, which are potential applications in mobile-phone-based facial recognition and surveillance cameras . Regarding dynamic range behavior, Sn-rich binary PVSK–PDs achieve an dynamic range of 100 dB (see Figure S11), which is better than that of commercial imaging sensors (∼60 dB) and is comparable to state-of-the-art wide-dynamic-range imaging sensors (∼100 dB). …”
Section: Resultsmentioning
confidence: 95%
“…The authors reported an over 87 dB SEHDR CIS with a 3.0 µm pixel introducing a high full-well capacity (FWC) photodiode (PD) and a multiple gain pixel technology [1][2][3][4]. In the previous sensor, photoelectrons accumulated in the photodiode are read out two times in different gains, then combined into an HDR signal.…”
Section: Introductionmentioning
confidence: 99%
“…Even with the 100 dB difference in the illumination levels, all the color objects are clearly captured without saturation. A. Tournier et.al [3] T. Yokoyama et.al [5] M. Kobayashi et.al [6] L. Stark et.al [9] T. Kondo et.al [8] I. Takayanagi et.al [13,14] Process…”
Section: Fabrication and Characterization Resultsmentioning
confidence: 99%
“…The charge storage region and the other driving circuits are located in the bottom layer. This SEHDR GS pixel was designed with three key technologies: (i) a multiple gain readout structure with additional BIN [12,13] and in-pixel capacitor; (ii) a high charge density PD [14]; (iii) the two sets of S/H capacitors for CDS operation in both high conversion gain (HCG) mode and low conversion gain (LCG) mode. The stacked pixel configuration with the two sets of different conversion gain signal storage realizes the GS operation with SE and ME HDR functions [9,13,14].…”
Section: New Stacked Bsi Voltage Domain Global Shutter Cmos Image Senmentioning
confidence: 99%